Identification of Non-Education Tutors Difficulty In Education Process Of Learning Study Groups - Nainggolan, Elizon; Irwan, Mahfuzi (Universitas Negeri Semarang, 2018)
This study aims to find out what are the difficulties of tutors who hold degrees non-educational in the learning process of study group in Binjai. This study used a descriptive qualitative research method with the research subjects were two tutors of learning groups holding non-education bachelor’s degrees in Binjai city which were determined purposively. Data collected by interview, observation and documentation techniques. Collected data is analyzed by steps: data reduction, data presentation, conclusion and verification. The results showed that in the package B learning group learning process in Binjai City, tutors with non-education degrees had many difficulties in the learning process. The conclusion that can be obtained in this study is the difficulties identified are located in: (1) the learning planning process, namely the difficulty in preparing RPP and syllabus. (2) the process of implementing learning, namely difficulties in preliminary activities, core activities (exploration, elaboration, confirmation), closing activities, and (3) assessment of learning outcomes.